Entrepreneurial thinking and Education 4.0 in communities with development gaps: an approach through the Sustainable Development Goals - Leiva-Lugo, Lorena; Álvarez-Icaza, Inés; López-Hernández, Francisco Javier; Miranda, Jhonattan (Frontiers in Education, 2024)
Entrepreneurial thinking is considered a desirable competency in the profile of today's professionals because it includes sub-competencies that strengthen individuals' leadership capacity and stimulate the development of creative solutions that present a high impact on society. However, it has been detected that disadvantaged communities located in areas with underdeveloped conditions and rural areas present a significant disparity in access to training models, current infrastructure, and activities that promote entrepreneurship compared to developed communities frequently found in large cities.Through a comparative analysis with quantitative methods, we seek to argue the need that these types of communities have. In addition, the design of a training model based on the design framework for Education 4.0 is presented; this training model seeks to train in the sub-competences of entrepreneurial thinking using the "push and pull" technique with the Sustainable Development Goals (SDGs) as its central axis). This seeks to close the existing gap, provide affordable resources to these types of disadvantaged communities, and, at the same time, promote local solutions through the SDGs. The study is conducted in the eastern region of Michoacán, Mexico, and will present the preliminary results.